Utilizing Xenogeneic Cells As a Therapeutic Agent for Treating Diseases. (12th May 2021) - Huang, Chi-Ping; Yang, Chi-Yu; Shyr, Chih-Rong
The utilization of biologically produced cells to treat diseases is a revolutionary invention in modern medicine after chemically synthesized small molecule drugs and biochemically made protein drugs. Cells are basic units of life with diverse functions in mature and developing organs, which biological properties could be utilized as a promising therapeutic approach for currently intractable and incurable diseases. Xenogeneic cell therapy utilizing animal cells other than human for medicinal purpose has been studied as a new way of treating diseases. Xenogeneic cell therapy is considered as a potential regenerative approach to fulfill current unmet medical needs because xenogeneic cells could be isolated from different animal organs and expanded ex vivo as well as maintain the characteristics of original organs, providing a versatile and plenty cell source for cell-based therapeutics beside autologous and allogeneic sources. The swine species is considered the most suitable source because of the similarity with humans in size and physiology of many organs in addition to the economic and ethical reasons plus the possibility of genetic modification. This review discusses the old proposed uses of xenogeneic cells such as xenogeneic pancreatic islet cells, hepatocytes and neuronal cells as a living drug for the treatment of degenerative and organ failure diseases. Novel applications of xenogeneic mesenchymal stroma cells and urothelial cells are also discussed. There are formidable immunological barriers toward successful cellular xenotransplantation in clinic despite major progress in the development of novel immunosuppression regimens and genetically multimodified donor pigs. However, immunological barriers could be turn into immune boosters by using xenogeneic cells of specific tissue types as a novel immunotherapeutic agent to elicit bystander antitumor immunity due to rejection immune responses. Xenogeneic cells have the potential to become a safe and efficacious option for intractable diseases and hard-to-treat cancers, adding a new class of cellular medicine in our drug armamentarium.